FAKTOR YANG MEMPENGARUHI WANITA USIA SUBUR(WUS) DALAM PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) : LITERATURE REVIEw - Theresia Mindarsih (STIKes CHMK, 2023)
Acetate Manual Inspection is an examination of the presence of pre-cancerous lesions on the cervix by smearing it with a 3-5% vinegar solution IVA examination is the easiest way to detect cervical cancer early. The purpose of this literature review is to find out the factors that influence IVA examination. The literature review method used is the literature review study method from articles that have been selected and analyzed from several sources so that they become a new discussion. The results of this literature study found 12 articles on factors that influenced the IVA examination, consisting of age, education, knowledge, occupation, role of officers, health services, access to information, income, husband's support, and attitude. Conclusion Based on the results of the analysis of the 12 articles conducted, the factors that influence the IVA examination are husband's support, attitude, role of officers, knowledge, education, access to information, and there is 1 article which analyzes the husband's support factor which does not affect WUS in the IVA examination Keywords: WUS, IVA